Pelatihan Perencanaan Keuangan Rumah Tangga Pada Desa Suka Nanti Kecamatan Kedurang Kabupaten Bengkulu Selatan - Yusnita, Yuli; Yolaga , Noda; Mojika , Nega (Universitas Dehasen Bengkulu, 2023)
Household financial planning training in Suka Nanti Village, Kedurang Sub-district, South Bengkulu Regency, is part of an effort to improve the financial literacy and welfare of rural communities. This study aims to evaluate the impact and effectiveness of the training program in improving household financial knowledge, skills and behavior. The research methods used included structured surveys, in-depth interviews and participatory observation to collect data before and after the training. The results showed a significant increase in people's knowledge and understanding of financial planning concepts after the training. In addition, the training also succeeded in changing the community's financial behavior, such as budgeting, saving regularly, and managing debt more wisely. The active involvement of the community in the implementation of the training was also a key factor in the success of this program. In conclusion, the household financial planning training in Suka Nanti Village had a positive impact on improving financial literacy and community welfare. The program not only provides individual benefits, but also strengthens social attachment and cohesion at the village level. Continued efforts in addressing emerging challenges are needed to ensure the long-term sustainability and effectiveness of the program.